Remineralization of Caries Lesions Extending into Dentin - ten Cate, J.M. (Journal of dental research, 2001)
Remineralization is one aspect of the overall process of tooth decay. However, it is primarily studied in shallow lesions. The aim of this study was to explore whether caries lesions in enamel and extending into the dentin can be remineralized. A single-section model was developed for the longitudinal and non-destructive monitoring of changes in enamel and dentin. Lesions at least 200 μm into dentin were formed in undersaturated acetate buffers. Next, the lesions were divided into groups (three treatment and one control) and remineralized. The treatments were: weekly immersion in 1000 ppm fluoride, single treatment with methanehydroxybisphosphonate, and a constant level of 1 ppm fluoride. De- and remineralization was assessed by transverse microradiography. Remineralization was observed in enamel, but also in dentin, indicating that, deep into dentin, the pores become supersaturated to apatite formation. Treatments affected remineralization only in the outer part of enamel. Both findings are explained by a relatively fast diffusion of mineral ions, with precipitation being rate-limiting. The results suggest that dentin remineralization, underneath enamel, can be achieved and could possibly be used in clinical treatment strategies.